2013
DOI: 10.1007/s10900-013-9715-8
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Underserved Populations Through Cancer Prevention and Early Detection

Abstract: It is well documented that cancer is disproportionately distributed in racial/ethnic minority groups and medically underserved communities. In addition, cancer prevention and early detection represent the key defenses to combat cancer. The purpose of this article is to showcase the comprehensive health education and community outreach activities at the H. Lee Moffitt Cancer Center and Research Institute (Moffitt) designed to promote and increase access to and utilization of prevention and early detection servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…These disparities in CPI seeking online are particularly concerning because comprehensive cancer centers charged with targeting communities with prevention initiatives do not have overarching strategies to disseminate CPI to cancer survivors and their families [76]. Researchers reported that when barriers to access are removed, the benefits of online information seeking are extended to individuals from underserved communities [24].…”
Section: Discussionmentioning
confidence: 99%
“…These disparities in CPI seeking online are particularly concerning because comprehensive cancer centers charged with targeting communities with prevention initiatives do not have overarching strategies to disseminate CPI to cancer survivors and their families [76]. Researchers reported that when barriers to access are removed, the benefits of online information seeking are extended to individuals from underserved communities [24].…”
Section: Discussionmentioning
confidence: 99%
“…Community advocacy refers to the actions of individuals and organizations on behalf of cancer patients, survivors and caregivers [37, 38]. Advocates at the community level include patients, family members, friends, and caregivers, as well as healthcare professionals and researchers [26].…”
Section: Community Advocacy: “Advocacy For Others”mentioning
confidence: 99%
“…In 2009, the program was formally named M-POWER to better reflect Moffitt's goal for cancer prevention and community outreach initiatives that address the health education and early detection needs among underserved populations. M-POWER works to empower these communities to make positive health choices and to increase screening behaviors by strengthening collaboration and partnerships, providing community-based health education/promotion, and increasing access to screening and care [17]. The program's guiding principles are rooted in cultural and linguistic competence, health education, community engagement, capacitybuilding, partnership development, and community-based participatory action.…”
Section: M-power Overviewmentioning
confidence: 99%
“…YMC is designed to focus on cancer prevention, early detection, and healthy lifestyles to increase breast cancer awareness and reduce breast cancer disparities among Hispanic women in the Tampa Bay region. The program is delivered by the H. Lee Moffitt Cancer Center and Research Institute (Moffitt) through its larger community engagement and outreach program focused on underserved populationsMoffitt Program for Outreach Wellness Education and Resources (M-POWER) [17]. The purpose of this paper is to showcase the YMC's innovative approaches and methods to cancer prevention and early detection, and to promote its use as an effective intervention for improving outcomes in community health education, outreach, and engagement activities and programs with Hispanic populations.…”
Section: Introductionmentioning
confidence: 99%